2013
DOI: 10.15343/0104-7809.2013372159165
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e promoção da saúde: em foco as gestantes

Abstract: Resumo AbstractThe aim of this study was to evaluate the Quality of Life of pregnant women attending the Family Health Strategy and identify the dimensions of Quality of Life better and worse evaluated. This is a descriptive, cross sectional study case, done in a Family Health Unit in the outskirts of São Bernardo do Campo. 42 women were evaluated using WHOQOLbref. The higher the score the better the assessment of Quality of Life. The scores of the domains were: Physical 57,65; Psychological 68,75; Environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
1
3
0
15
Order By: Relevance
“…Health promotion is part of a new health care model that aims at the quality of life of populations, understanding it as a result of a set of determinants of socioeconomic, political, cultural and psychological context that influence society, not being restricted only to the biological field (6) . In this sense, the evaluation of the quality of life becomes an important care management tool and can help to measure and analyze the health promotion actions in progress and that ones that could be implemented in communities and health programs (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Health promotion is part of a new health care model that aims at the quality of life of populations, understanding it as a result of a set of determinants of socioeconomic, political, cultural and psychological context that influence society, not being restricted only to the biological field (6) . In this sense, the evaluation of the quality of life becomes an important care management tool and can help to measure and analyze the health promotion actions in progress and that ones that could be implemented in communities and health programs (7) .…”
Section: Discussionmentioning
confidence: 99%
“…This instrument allows describing the subjective perception of individuals in relation to their physical and psychological health, social relationships and the environment in which they live 8 . It is observed that several studies performed in Brazil evaluated the QOL of individuals in specific populations, such as the elderly and pregnant women, [9][10][11] or in those with different health problems [12][13][14] . On the other hand, few studies have evaluated the QOL of the general population, with different health profiles, such as those attended by the Primary Health Care (PHC) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A promoção da saúde da gestante e do feto deve ser feita por meio de boa assistência pré-natal. O início do pré-natal deve ocorrer o mais precocemente possível, assegurando abordagens adequadas em todo o período gestacional, sem impacto para a saúde da mãe e possibilitando o nascimento de um recém-nascido saudável 7 .…”
Section: Discussionunclassified